A dimensão atitudinal da acessibilidade e da hospitalidade a pessoas com deficiência e com mobilidade reduzida sob a perspectiva de um corpo coletivo acolhedor : o destino turístico Balneário Camboriú/Santa Catarina/Brasil - Franzen, Letícia Indart (My University, 2024)
The present research proposes as a general objective to identify and analyze configurations that assume the attitudinal dimension of accessibility for People with Disabilities (PWDs) and People with Reduced Mobility (PRMs) on the edge of Praia Central de Balneário Camboriú, SC/BR, under the perspective of a Corpo Coletivo Acolhedor (CCA). This work discusses the concept of accessibility based on hospitality/welcome relationships, as conceived by Perazzolo, Santos and Pereira (2013), and their attitudinal aspects. Methodologically, the qualitative research, with a hermeneutic approach, was developed from two perspectives: initially, documentary, with analysis of the laws and norms that refer to accessibility and in the "listening and meaning" stage, voice was given, through semi-structured interviews, with 19 subjects involved in the three dimensions of the CCA ("Managing Organization", "Services" and "Culture") and tourists. To organize and analyze the data, content analysis techniques were used, according to Bardin (2000) and enunciative analysis, according to Bakhtin (1997). From the discursive outlines, 3 categories of analysis were identified (Accessibility, Hospitality, Experiences lived or observed) that explicitly express their discomfort with issues of accessibility to PWDs and PRMs. As considerations, the speeches of the interviewed subjects mark a space that is still tense in the triangulation of the vertices "Managing Organization", "Services" and "Culture". A "push and shove" game was identified: the Corps recognizes its flaws and bottlenecks, but none of the vertices takes on the responsibility of thinking and acting regarding the rights of PWDs and PMRs. This reflective path makes it possible to conclude that, in a panoramic view, the main point to which the analyzed texts (laws and norms) converge falls on tangible elements of accessibility, so that intangible elements, even if associated with the quality of life and citizenship of these people, are not established as central elements of definitions and characterizations, which is aggravated by temporal lags, or even identified conceptual inconsistencies. [resumo fornecido pelo autor]
A presente pesquisa propõe-se como objetivo geral identificar e analisar configurações que assume a dimensão atitudinal da acessibilidade a Pessoas com Deficiência (PCDs) e a Pessoas com Mobilidade Reduzida (PMRs) na orla da Praia Central de Balneário Camboriú, SC/BR, sob a perspectiva de um Corpo Coletivo Acolhedor (CCA). Este trabalho discute o conceito de acessibilidade a partir de relações de hospitalidade/acolhimento, conforme as concebem Perazzolo, Santos e Pereira (2013), e de seus aspectos atitudinais. Metodologicamente, a pesquisa, de natureza qualitativa, com abordagem hermenêutica, desenvolveu-se a partir de duas perspectivas: inicialmente, documental, com análise das leis e normas que se referem à acessibilidade e na etapa "escuta e significação" deu-se voz, por meio de entrevista semiestruturadas, a 19 sujeitos afetos às três dimensões do CCA ("Organismo Gestor", "Serviços" e "Cultura") e a turistas. Para a organização e análise dos dados, foram utilizadas técnicas da análise de conteúdo, conforme Bardin (2000) e análise enunciativa, de acordo com Bakhtin (1997). A partir dos traçados discursivos, identificaram-se 3 categorias de análise (Acessibilidade, Hospitalidade, Experiências vividas ou constatadas) que, explicitamente, manifestam seu desconforto com as questões de acessibilidade às PCDs e PMRs. Como considerações, as falas dos sujeitos entrevistados marcam um espaço ainda tensionado na triangulação dos vértices "Organismo Gestor", "Serviços" e "Cultura". Identificou-se um jogo de "empurra-empurra": o Corpo reconhece suas falhas e seus gargalos, mas nenhum dos vértices chama, para si, a responsabilidade de pensar e agir a respeito dos direitos das PCDs e PMRs. Este percurso reflexivo possibilita concluir que, numa visão panorâmica, o ponto principal para o qual convergem os textos analisados (leis e normas) recai sobre elementos tangíveis da acessibilidade, de sorte que elementos intangíveis, ainda que associados à qualidade de vida e à cidadania dessas pessoas, não se instituem como elementos centrais das definições e caracterizações, o que é agravado pelas defasagens temporais, ou mesmo incongruências conceituais identificadas. [resumo fornecido pelo autor]
Keywords: Turismo - Camboriú (SC); Pessoas com deficiência - Orientação e mobilidade; Hospitalidade - Camboriú (SC); Tourism - Camboriú (Brazil); People with disabilities - Orientation and mobility; Hospitality - Camboriú (Brazil)